Constraining the area of rapid and deep‐seated exhumation at the St. Elias syntaxis, Southeast Alaska, with detrital zircon fission‐track analysis. Issue 5 (1st May 2014) - Falkowski, Sarah; Enkelmann, Eva; Ehlers, Todd A.
Abstract The Chugach‐St. Elias orogen, Southeast Alaska/Southwest Yukon, formed in response to the ongoing Yakutat microplate subduction‐collision with the North American Plate. Due to heavy glaciation, the region is a prime location to study active convergent orogenesis and climate‐tectonic interactions. This study focuses on the long‐term distribution of deformation in the St. Elias syntaxis area, where dextral motion along the plate‐bounding Fairweather Fault transitions into convergence. We present 2718 new zircon fission‐track single‐grain ages from 26 glaciofluvial outwash samples. The grain ages range from 293 Ma to 0.2 Ma, and each sample contains two to five age populations with peaks between 267 ± 64 Ma and 1.2 ± 0.7 Ma (1σ). The rocks of the Yakutat microplate are dominated by latest Cretaceous and Eocene fission‐track ages, while the rocks of the North American Plate in the syntaxis region reveal two exhumation phases at 5.1 Ma and 2.7 Ma. The spatial pattern of ≤5 Ma cooling ages shows that the area of rapid and deep exhumation at the St. Elias syntaxis is more extensive than previously known and confined to the south by the Fairweather Fault, to the west by the Seward Glacier catchment, and to the east possibly by the inferred Connector Fault. The area seems to be 4800 km2 large and may extend farther to the north. The new zircon fission‐track data further suggest a transpressional plate boundary since 30 Ma and the onset of plate collision 15–12 Ma.